Research Trends in Transformative School Leadership: A Systematic Review and Bibliometric Analysis - Dedeh Nurhayati; Rahmat Rahmat; Kokom Komalasari; Junaidi Junaidi (Yayasan Keluarga Guru Mandiri, 2026)
It is commonly acknowledged that transformational leadership is an essential framework for understanding how school principals enhance teacher motivation, performance, and overall school development across a variety of settings. However, despite its proven advantages, the current body of research remains dispersed across methodological, institutional, and cultural boundaries, highlighting the necessity of an integrated synthesis. This study uses a hybrid methodological approach that combines a Systematic Literature Review (SLR) with bibliometric analysis using VOSviewer to map the trends, themes, and research fronts of transformational leadership among school principals. Using data from Scopus and PRISMA-guided methods, the study identifies networks of collaboration, intellectual structures, and new directions that influence the creation of theories, leadership development programs, and policy in educational leadership. According to the findings, transformational leadership has developed into a multifaceted framework that includes teacher empowerment, emotional intelligence, and adaptive digital competence, rather than being solely focused on morality and justiceThough it is constrained by its reliance on Scopus and English-language sources which may exclude important regional perspectives the integration of SLR and bibliometric methods offers a thorough understanding of the conceptual and empirical development of transformational leadership. This study emphasizes the importance of incorporating inclusiveness, ethical reasoning, and reflective practices into the development of policies and leadership training. Therefore, to better understand how transformational leadership concepts are contextually adjusted across various educational systems and cultural contexts, future research should examine longitudinal and cross-national studies.